Интеллектуальная собственность: законодательство и практика применения: практическое пособие / В. В. Белов, Г. В. Виталиев, Г. М. Денисов - Белов Владимир Владимирович (Institutiones)
Экземпляры: аб. (2007) / Инвентарный номер: 50663 / Цена: / Сис.шифр: 67.404.3 / Авт.знак: Б 43 / ГРНТИ: 10.27 / ББК: 67.404.3